Role of gendered poverty in sustainable development in South Asia. (3rd June 2019) - Soni, Pooja; Bakhru, Kanupriya Misra
As world modernisation progresses with technology and expansion of business opportunity via globalisation many economist, environmentalist and NGOs have raised their concern towards depleting natural resources and shared common thoughts on urgent need to focus on sustainable development attempts globally. One impending factor is poverty that is both a cause and outcome of poor sustainable development. This paper works towards analysing the impact of poverty, more especially gendered poverty on sustainable development. It creates to develop trend overtime of women discrimination and inequality across demography leading to gender poverty in South Asian region. It also builds theory towards importance of gender equality economically and in socio-cultural terms for environment restoration.